A comprehensive study: Theoretical and experimental investigation of heteroatom and substituent effects on frontier orbitals and polymer solar cell performances. Issue 19 (7th September 2020) - Cevher, Sevki Can; Hizalan, Gonul; Alemdar Yilmaz, Eda; Cevher, Duygu; Udum Arslan, Yasemin; Toppare, Levent; Yıldırım, Erol; Cirpan, Ali
Abstract: Benzochalcogendiazole derivatives are incorporated with thieno[3, 4‐ c ]pyrrole‐4, 6‐dione (TPD) acceptor and 4, 8‐diethoxybenzo[1, 2‐ b :4, 5‐ b ′]dithiophene donor to synthesize tree‐component random copolymers. Four different copolymers are synthesized and their electronic, optical and photovoltaic properties are compared. Comparisons are aligned in the course of two different strategies, which are the replacement of benzochalcogendiazole moiety and the modification of side group on benzothiadiazole. Theoretical calculations by comparing the HOMO‐LUMO levels, band gaps and other electronic descriptors of pristine and 2 + 2 two acceptor‐based copolymers are investigated. Random copolymer bearing benzoxadiazole moiety, PO exhibits the highest photovoltaic performance of 8.29% with a J sc of 14.96 mA cm −2, V oc of 0.87 V, fill factor (FF) of 63.70%. PF possesses the highest V oc with a value of 0.88 V, J sc of 14.40 mA cm −2, power conversion efficiency (PCE) of 7.32% with 58% FF. PS exhibits average feature with J sc 11.82 mA cm −2, V oc 0.80 V, FF 50%, and 4.72% PCE. Lowest performing selenadiazole containing random copolymer (PSe) copolymer exhibits maximum PCE as 3.65%. These results demonstrate the promising effectiveness of benzoxadiazole selection as an alternative acceptor unit and F atom substitution for the design of (A1‐D)‐(A2‐D) type random copolymers for organic solar cells. Abstract : Experimental and theoretical investigation of tuning the frontier orbitals of benzochalcogendiazole derivatives containing random conjugated polymers were investigated for high performance photovoltaic devices. Two different strategies were employed: single atom substitution on benzochalcogendiazole and altering the substituent of benzothiadiazole. Photovoltaic performances of individual polymers in polymer:PCBM conventional devices were investigated.